Kanata/Canada: Re-storying Canada 150 at the Canadian Museum for Human Rights - Duhamel, Karine (Journal of the Canadian Historical Association / Revue de la Société historique du Canada, 2017)
“Kanata/Canada: Re-storying ‘Canada 150’ at the Canadian Museum for Human Rights” seeks to contextualize the changing role of museums and of heritage institutions within contemporary discussions about the urgent need for public education on Indigenous histories and contemporary realities. The author of this article argues that museums can become truly decolonizing spaces if they are willing to re-examine their own purpose and mandate. Through an examination of the CMHR’s own exhibition development for 2017, she maintains that undertaking grounded, reparative reconciliation that is meaningful to communities in a museum context means going beyond acknowledgement and recognition to re-storying the very foundations of Canadian nation-building, and of projects like Confederation that remain, necessarily, unfinished.